Acute Soft Head Syndrome as the Initial Presentation of Sickle Cell Disease in an Adolescent in Rural Western Uganda: Case Report - Abukar Ali Ahmed; Dalton Kambale Munyambalu; Awil Abdulkadir Abdi; Elias Joseph Xwatsal; Hanan Asad Hassan; Ibrahim Ahmed Nur; Abdikani Ali Hassan; Venance Emmanuel Mswelo (BioMed Target Journal)
Sickle haemoglobin (HbS) is the most common abnormal haemoglobin mutation worldwide. In Uganda, according to the Uganda Sickle Surveillance Study (US3), the overall prevalence of sickle cell trait and disease is 13.3% and 0.7%, respectively. SCD presents with numerous complications. Acute Soft Head Syndrome (ASHS) or sickle cell cephalohematoma is among the rare complications of SCD. We report a 14-year-old adolescent male, a resident of rural Western Uganda, who presented with a history of non-traumatic painless scalp swelling for a week and multiple joints pain for 5 days. He had a similar swelling in the previous six months, which subsided after blood transfusion given at a nearby health facility. There was a history of on-and-off fever, easy fatiguability, and generalized body weakness. Complete blood counts revealed anemia, Haemoglobin Electrophoresis confirmed Sickle Cell Anemia. Head Computed Tomography concluded a subgaleal fluid collection. The diagnosis of acute soft head syndrome was established in a newly diagnosed SCD patient. This case highlights a rare diagnosis of acute soft head syndrome as well as a late diagnosis of SCD in adolescent in rural settings. In such settings, the pre-existing poor socio-economic background coupled with atypical presentation constitute a major impediment for timely diagnosis.